Beyond Bones: Assessing Whether Ultrasound‐Aided Instruction and Practice Improve Unassisted Soft Tissue Palpation Skills of First‐Year Medical Students. (18th December 2018) - Walrod, Bryant J.; Boucher, Laura C.; Conroy, Mark J.; McCamey, Kendra L.; Hartz, Clinton A.; Way, David P.; Jonesco, Michael A.; Albrechta, Steven; Bockbrader, Marcia; Bahner, David P.
Abstract : Objectives: Our purpose was to determine whether ultrasound (US)‐aided instruction and practice on musculoskeletal anatomy would improve first‐year medical students' ability to locate and identify specific soft tissue structures by unaided palpation in the upper and lower extremities of healthy human models. Methods: This study was a randomized crossover design with 49 first‐year medical students randomly assigned to 1 of 2 groups. Each group was provided expert instruction and hands‐on practice using US to scan and study soft tissue structures. During session 1, group A learned the anatomy of the upper extremities, whereas group B learned the lower. Students were then tested on their proficiency in locating 4 soft tissue structures (2 upper and 2 lower extremities) through palpation of a human model. During session 2, group A learned lower extremities, and group B learned upper. At the end of session 2, students repeated the assessment. Results: After the first instructional session, neither group performed significantly better on identifying and locating the soft tissue landmarks they learned aided by US. After the second instructional session, however, scores for both groups increased approximately 20 percentage points, indicating that both groups performed significantly better on palpating and identifying both the upper and lower extremity soft tissue landmarks (Cohen d = 0.89 and 0.82, respectively). Conclusions: Time and practice viewing soft tissue structures with US assistance seems to have a "palpation‐with‐eyes" effect that improves students' abilities to correctly locate, palpate, and identify limb‐specific soft tissue structures once the US assistance is removed.